Media coverage of darknet market closures: assessing the impact of coverage on US search and Tor use activity. - Jardine, Eric; Cruz, Sarah; Kissel, Heather (Crime, Law & Social Change, 2023)
Darknet cryptomarkets are a common method of drug procurement and are frequently a focal point for law enforcement intervention as a result. Past works assessing the effectiveness of cryptomarket closures by law enforcement have found a high degree of ecosystem resilience. Previous work, however, has not parsed the potential mediating role that official press statements and media coverage of such events might play on subsequent behavior. Using a new dataset of 27,195 distinct deterrent- or publicity-related sentiment-expressive signals taken from 406 media stories and 47 official press releases between 2013 and 2019, this article traces the potential impact of law enforcement closure of Darknet cryptomarkets on both US Google search activity and US Tor network use. The results generally show: 1) that discussion of certainty and severity of punishment, as deterrent signals, and sensationalism and market resiliency, as publicity signals, are the most forcefully expressed sentiments in the corpus of text; 2) US Google search interest in the Dark Web topic exhibits a fair degree of periodicity that is largely unassociated with the sentiment expressed in media coverage; and 3) US Tor anonymity network usage tends to be somewhat sensitive to how the closure is framed, with drops in Tor client connections in the US following comparatively high deterrence-coverage events and increases in the same following comparatively high publicity closures.